LINGUOCULTURAL ANALYSIS OF “FREEDOM” AND “LIBERTY” NOTIONS BY THE EXAMPLE OF THE STATUE OF LIBERTY (American Journal of Interdisciplinary Research and Development, 2023)
Two notions, freedom and liberty has always been controversial topic in the field of linguo-conceptual study. Although they have similar meanings, several differential meanings can also be identified. The following article is going to analyse a number of idiosyncrasies by exampling “the Statue of Liberty” in American linguo-culture.